2018
DOI: 10.1038/s41598-017-18812-x
|View full text |Cite|
|
Sign up to set email alerts
|

Labile organic carbon pools and enzyme activities of Pinus massoniana plantation soil as affected by understory vegetation removal and thinning

Abstract: The effects of forest management on carbon (C) sequestration are poorly understood, particularly in the Three Gorges Reservoir area. We aimed to identify the effects of forest management on C sequestration in Pinus massoniana plantations. An intact control forest (CK), a site undergoing regular shrub cutting with the simultaneous removal of residues (SC), a site under low-intensity thinning (LIT), and a site under high-intensity thinning (HIT) were compared for soil labile organic carbon (LOC), related enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Total phosphorus (TP), total potassium (TK), available phosphorus (AP), and available potassium (AK) were measured using an inductively coupled plasma mass-spectroscopy (ICP-MS) analyzer (IRIS Intrepid II XSP, Thermo Fisher Scientific Co., Waltham, MA, USA) [53]. Soil pH was measured from a soil:water suspension (1:5 w/v) [54]. The basic physical and chemical properties of the experimental soil are shown in Table 1.…”
Section: Sapling Preparation and Stress Treatmentsmentioning
confidence: 99%
“…Total phosphorus (TP), total potassium (TK), available phosphorus (AP), and available potassium (AK) were measured using an inductively coupled plasma mass-spectroscopy (ICP-MS) analyzer (IRIS Intrepid II XSP, Thermo Fisher Scientific Co., Waltham, MA, USA) [53]. Soil pH was measured from a soil:water suspension (1:5 w/v) [54]. The basic physical and chemical properties of the experimental soil are shown in Table 1.…”
Section: Sapling Preparation and Stress Treatmentsmentioning
confidence: 99%
“…Such feedbacks are common in forest ecosystems, where different tree species are associated with distinct microbial communities that exhibit significant functional differences in terms of extracellular enzyme production and nutrient cycling (Ribbons et al, 2016;Weand et al, 2010). Similarly, forest understory shrubs and herbaceous vegetation can influence microbial community structure and function, even within the same forest type (Burke et al, 2011;Fu et al, 2015;Shen et al, 2018;Wurzburger and Hendrick, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Proposed R. maximum management strategies include mechanical removal of the R. maximum understory and subsequent use of herbicides to suppress stump sprouting (Vose et al, 2013). Soil responses to understory vegetation removal are challenging to predict, with prior studies reporting positive, negative, and neutral responses of soil C and N, microbial biomass, fungal:bacterial (F:B) ratios, and extracellular enzyme activities in response to forest understory removal (Boerner et al, 2008;Giai and Boerner, 2007;Shen et al, 2018;Wu et al, 2011;Zhao et al, 2011). A prior R. maximum removal study in the southern Appalachian region showed modest increases in soil inorganic N with no evident effects on soil microbial biomass or invertebrate communities (Wright and Coleman, 2002;Yeakley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As the availability of water and nutrients increases, more nutrient elements are accumulated in soil microbial biomass [4,10,37]. For example, Shen et al (2018) [14] observed increases in SOC, STN, and STP after thinning. Yang et al (2017) [11] and Kim et al (2018) [43] suggested a positive influence of thinning on the soil microbial biomass.…”
Section: Variation Of Soil Properties and Stoichiometry Following Thimentioning
confidence: 99%